PERAN SUPERVISI AKADEMIK DALAM MENINGKATKAN PROFESIONALISME GURU MTS TMI PUTRA AL-AMIEN PRENDUAN - Wadi, Namlul (PILAR, 2024)
This research discusses the importance of discipline in daily life, especially regarding Arabic language discipline in an educational environment. Discipline is an integral part of life, especially in schools and Islamic boarding schools. The study explores the implementation and influence of Arabic language discipline on fifth-grade female students at DIA A TMI Putri Al-Amien Prenduan Sumenep Madura. The research method used a qualitative approach with a case study and involved observation, interviews, and documentation. The results indicate that academic supervision, especially in Arabic language teaching, plays an important role in improving teacher professionalism and Arabic language discipline among female students. Supporting factors include motivation from the school principal and supportive facilities, while inhibiting factors include differences in teacher abilities and a shortage of supervisors. The research results show that the appropriate role of academic supervision and a supportive educational environment contribute to the formation of strong Arabic language discipline and positive influences on the daily lives of female students.